Some records of Ethiopia, 1593-1646 : being extracts from the history of high Ethiopia or Abassia by Manoel de Almeida together with Bahrey's history of the Galla /: being extracts from the history of high Ethiopia or Abassia by Manoel de Almeida together with Bahrey's history of the Galla. (2017) - Huntingford, G.W.B
No abstract available